Magnesium Infusion on Dental Implants and Its Impact on Osseointegration and Biofilm Development: A Review - Widyasrini, Dyah Anindya; Annisa, Mutiara; Sunarintyas, Siti; Samaranayake, Lakshman; Siswomihardjo, Widowati (European Journal of Dentistry, 2025)
Dental implants have gained global popularity as a treatment option for tooth loss. The success of dental implants depends on their optimal integration into the tissues of the alveolar bone and the periodontium. However, several factors can hinder the proper osseointegration of implants, with the growth of biofilm on the implant surface and subsequent peri-implant infections being significant concerns. To overcome this challenge, researchers have explored the incorporation of antimicrobial agents onto metallic implant surfaces to mitigate biofilm growth. Ideally these agents should promote osteogenesis while exhibiting antibacterial effects. Magnesium (Mg) has emerged as a promising dual-function implant coating due to its osteogenic and antibacterial properties. Despite several studies, the precise mechanisms behind osteoinductive and antimicrobial effect of Mg is unclear, as yet. This review aims to collate and discuss the utility of Mg as a dental implant coating, its impact on the osteogenic process, potential in mitigating microbial growth, and prospects for the future. A comprehensive literature search was conducted across several databases and the findings reveal the promise of Mg as a dual-function dental implant coating material, both as a standalone agent and in combination with other materials. The antibacterial effect of Mg is likely to be due to its (1) toxicity particularly at high concentrations, (2) the production or reactive oxygen species, and (3) pH modulation, while the osteoinductive effect is due to a complex series of cellular and biochemical pathways. Despite its potential both as a standalone and composite coating, challenges such as degradation rate, leaching, and long-term stability must be addressed. Further research is needed to understand the utility of Mg as an implant coating material, particularly in relation to its antibacterial activity, osseointegration, and longevity in the oral milieu.
Keywords: magnesium; dental implant; coating; osteoinductive; antibacterial